TEACHER TEACHING STYLES IN INTRODUCING CONCEPT MAPPING STRATEGY IN READING COMPREHENSION ACTIVITY AT SENIOR HIGH SCHOOLS IN MEUREUDU, ACEH - Khairiah Syahabuddin; Rahmat Yusny; Nia Zahara (Englisia: Journal of Language, Education, and Humanities, 2019)
The objective of this study is to learn how English teachers’ teaching style at Senior High Schools (SMAs) in Meureudu in introducing concept mapping strategy in delivering reading comprehension lesson. In teaching Reading Comprehension, different teaching styles gives different students learning experience and output, and using concept mapping, students are stimulated to have better control over their comprehension. This study was conducted at SMA 1 Meureudu and SMA 2 Meureudu, a town located 123 kms from Banda Aceh, Indonesia. Very often, English classes in schools located far from the main cities in Aceh suffer from lack interesting activity The study was using qualitative approach through class activity observations and interviews. Concept mapping activities facilitated by the teachers at SMA 1 Meureudu used digital projector and paper handouts as the media for the group activities. The teacher of SMA 2 Meureudu used only handout paper as a medium and by pairing the students. The findings of this study showed that the teaching styles in delivering reading activity using the concept mapping activity used by the teachers in both schools differ in the way how the teacher assign student to work on the task. The students were found to be more fully engaged in the reading activity with concept mapping compared to any past reading activities using translating line-by-line and answering questions. Assigning group reading task also help boost the students motivation and collaborative responsibility to learn.